Design entrepreneurship as teaching methodology / Thomas Cline - Cline, Thomas (2019)
As more design students plan for non-traditional jobs in the gig economy, it seems prudent to accommodate their educational needs within traditional models of design education. While most forms of design education are focused on producing designers that join traditional design firms, we should also accommodate those students who wish to work on task-based projects or open their own firms. Having found this additional content difficult to fit into the current curriculum, we have begun a student-centered design incubator and consultancy that allows our students to learn by doing-by becoming design entrepreneurs while remaining sheltered by the resources of the university. Louisiana Design Works provides educational and physical resources to students who wish to establish their own design-centered enterprises. These enterprises can take many forms; freelance opportunities, consultancies, graphic design firms, photography studios, and small-scale design and fabrication shops. It is through Louisiana Design Works that we teach our students skills beyond those typical to an undergraduate design education. They learn, in a very hands-on way, to research, design, market and manage their businesses, and manufacture and/or provide the services specific to their individual goals and aspirations. In creating this opportunity, we are able to promote, and retain, local designers and the products and services that they produce. In this way, we contribute to educational practices, economic growth, and community prosperity. While we do not yet have sufficient data to make substantial claims, we hold that this methodology is worth further exploration and would encourage others to adopt such a model of education.